2018
DOI: 10.1002/anzf.1325
|View full text |Cite
|
Sign up to set email alerts
|

Relationship and Family Therapy for Newly Resettled Refugees: An Interpretive Description of Staff Experiences

Abstract: The needs of refugees are of crucial concern internationally. Relational trauma is an area that is particularly under-emphasised and under-researched. The Strength to Strength program (STS) was a relationship and family counselling service for recently arrived refugees in Sydney, Australia. The service model built on post-Milan systemic family therapy principles to include cultural and trauma-informed aspects of care. This study explored the design and impact of the program, through qualitative accounts provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 55 publications
(97 reference statements)
0
12
0
Order By: Relevance
“…Notable exceptions included Harden et al’s (2015) work with young people in minority communities who experienced community violence and Muenzenmaier, Margolis, Langdon, Rhodes, Kobayashi & Rifkin’s (2015) work with women experiencing serious mental illness. Karageorge et al’s (2018) work with ‘newly resettled refugees’ acknowledged the collective nature of trauma experienced by people who experience forced migration, but an overt critical or anti-oppressive approach was not evident. Muenzenmaier et al (2015) combined a trauma informed approach with the critical concept of intersectionality to acknowledge the layering up of traumatic experiences that can occur due to race, gender, ethnicity, socioeconomic status, immigration and severe child abuse.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Notable exceptions included Harden et al’s (2015) work with young people in minority communities who experienced community violence and Muenzenmaier, Margolis, Langdon, Rhodes, Kobayashi & Rifkin’s (2015) work with women experiencing serious mental illness. Karageorge et al’s (2018) work with ‘newly resettled refugees’ acknowledged the collective nature of trauma experienced by people who experience forced migration, but an overt critical or anti-oppressive approach was not evident. Muenzenmaier et al (2015) combined a trauma informed approach with the critical concept of intersectionality to acknowledge the layering up of traumatic experiences that can occur due to race, gender, ethnicity, socioeconomic status, immigration and severe child abuse.…”
Section: Resultsmentioning
confidence: 99%
“…Creatively combining culturally familiar and "safe" activities such as music making, cooking, or sport with unfamiliar or challenging tasks can be a way of safely extending participants' threshold for discomfort. Karageorge et al (2018) found that culturally familiar interest-based group activities were supportive for people who experienced forced migration related trauma and ongoing relational trauma during resettlement. The groups allowed participants to "get to know each other, to come out of their spaces and to know the community'".…”
Section: Promoting Cultural and Personal Safetymentioning
confidence: 98%
See 3 more Smart Citations